IR780 Based Sonotherapeutic Nanoparticles to Combat Multidrug-Resistant Bacterial Infections - Huang, Biying; Wang, Long; Tang, Kui; Chen, Sijie; Xu, Yan; Liao, Haiqin; Niu, Chengcheng (Frontiers in Chemistry, 2022)
Multidrug-resistant (MDR) bacterial strains have emerged and weaken the therapeutic effects of antibacterial drugs. Sonodynamic therapy (SDT) takes advantage of noninvasiveness and deep tissue-penetrating features and has been rejuvenated to combat MDR bacteria and their biofilm associated infections. To improve the efficacy of antibacterial SDT, we first developed IR780 based PLGA nanoparticles as sonosensitizers for high-frequency ultrasound (US)-monitored antibacterial SDT of MRSA myositis by therapeutic low-frequency US. In this study, the developed shell-core structured IR780@PLGA nanoparticles were designed with a polymer shell PLGA with the sonosensitizer IR780 loaded on. High frequency diagnostic US was introduced to monitor the sonotherapeutic progression of bacterial myositis by therapeutic low-frequency US. Importantly, the in vitro and in vivo results confirmed that IR780@PLGA nanoparticles combined with US irradiation possess high efficiency for antibacterial therapy. This approach provides a simple and efficient strategy to monitor and combat MDR bacterial infection.